HUBUNGAN ANTARA KARAKTERISTIK RUMAH TANGGA DENGAN PARTISIPASI DALAM KELUARGA BERENCANA DI PROVINSI JAMBI : Analisis Data SDKI 2007 - -, Suandi (PIRAMIDA, 2012)
The purpose of the study are (1) studying of the socio demographic, socioeconomicof households, and the participation of family planning in JambiProvince, and (2) analyze the influence of socio-demographic, socio-economic ofhousehold on the level of participation on family planning. Design research is thedocumentation. Research variables are age of respondent, educational level,residence, wealth index, the child was still alive and variable levels participationof family planning. The research data was sourced from secondary data drawnfrom the data results Indonesian Demographic and Health Survey (IDHS), theNational in 2007. To know the relevance factor of respondents age, educationlevel, residence, wealth index, and factors of number of living children on thelevel of participation of family planning analyzed using Chi-Square test (?2).The results showed that the prevalence rates of family planning in Jambi Provincereached 61.41 percent. The analysis showed that factors characteristic of thenumber of living children positively associated with participation family planningfor couples of childbearing age (PUS) in Jambi Province. That is, the more of thenumber of living children who owned the PUS have a positive and significantimpact on participation family planning, while the characteristic factors of age,educational level, area of residence, and factors characteristic of welfare indexshowed no association relationship on family planning participation.
Keywords: family planning participation, household characteristics, couples of childbearing age, and number of living children